(untitled) (Research, Society and Development, 2022)
Objective: the aim of this article was to evaluate the level of knowledge of dental students and dentists, as well as the efficiency and applicability of an online Quiz as a methodology for teaching dentistry. Material and methods: a cross-sectional study was carried out, using an online Quiz containing questions with “fact” and “fake” response options. After answering the questions, the platform used automatically provided the correct answer with the respective bibliographic references. Dentistry students and professionals in the field responded to the survey, totaling 88 responses. This research was approved by technical opinion 51677621.6.0000.5257 CEP-HUFF/UFRJ. Results: the average result was 76.5% of correct answers. In addition, out of a total of 4890 views, only 88 responses were obtained completely. Conclusion: It was observed that dentistry students and dentists have a reasonable knowledge about the dental theme related to COVID-19 and that active teaching methodologies need better implementation in universities.